(untitled) (AYUSHDHARA, 2021)
This review concerns the appropriate study of X-ray Photo-electron Spectroscopy to analyze oxidation states in the herbo-mineral drugs. It describes multivalent forms of silver and silver based drugs. Silver exhibits multivalent forms with various phases like AgO, Ag2O and Ag2O3 etc. Silver Bhasma is one of the potent Ayurvedic drug from herbo-metallic combinations. This traditional preparation is used for treating various ailments such as disorders related to eye and nerve, brain functioning and tuberculosis etc. Mixture of silver metal and herbal ingredients passes through Bhasmikarana method and then gets converted into organo-metallic complex i.e. silver Bhasma. The preparation method of Bhasmas aims at removing injurious substances which are foreign to the body from metals. The process of Bhasmikarana transferred the material from its inorganic state to the organic; therefore the assimilation of the substances for their therapeutic use will be easier in the human body. Silver Bhasma plays an essential role in Ayurvedic therapeutics due to its versatile qualities. Therefore, if a Bhasma is to be considered as a standard one, X-ray photoelectron spectroscopy should be one of the essential methods. Scanning electron microscope (SEM) technique was used to detect morphology of silver based Bhasmas and Energy dispersive X-ray spectroscopy (EDAX) detected elemental analysis. X-ray photoelectron spectroscopy is the useful platform to detect important chemical constituents as per their required oxidation states which are essential part in therapeutic use.